Adrenaline - BRIAN B. HOFFMAN (arvard University Press, 2013)
Adrenaline has enormous cultural signifi cance as a molecule associated with medically important stress and with excitement, anger, and terror. Adrenaline flows in an adventurer ascending a sheer cliff or in a young violinist debuting at Carnegie Hall. A shot of adrenaline empowers superhuman feats in emergencies. Risk takers seeking dangerous recreations are adrenaline junkies who enjoy repetitive adrenaline rushes. On the other hand, an adrenaline surge during a bitter argument may precipitate a heart attack or scare us to death.